Geographic distribution and apparent decline of Crotalus durissus terrificus (Laurenti 1768; Serpentes, Viperidae) in Uruguay - Prigioni, Carlos M. (2013)
Herein, we make a comprehensive account of rattlesnake records in this country obtained from herpetological literature and other bibliographic sources, specimens accessioned in herpetological and non-specialized local collections, and new information gathered during field surveys.